Lithium ion secondary battery

By adjusting the composition of the base film and electrolyte, the problem of poor cold start performance of lithium iron phosphate batteries at low temperatures is solved, and the excellent performance and safety performance of the batteries are improved at high and low temperatures.

CN119447417APending Publication Date: 2025-02-14ZHUHAI COSMX POWER BATTERY CO LTD

Patent Information

Application Number
CN202411568465.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing 12V lithium iron phosphate battery has poor cold start performance at low temperatures, which affects the battery's discharge capacity and start performance.

Method used

By adjusting the porosity of the base film, the ratio of lithium difluorosulfonimide and lithium hexafluorophosphate in the electrolyte, and the ratio of linear organic solvents and cyclic organic solvents, the composition of the electrolyte is optimized and the transmission efficiency of lithium ions is improved.

Benefits of technology

It significantly improves the cold start performance of lithium iron phosphate batteries at low temperatures, takes into account high and low temperature performance, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447417A_ABST
    Figure CN119447417A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and provides a lithium ion secondary battery. The battery comprises a positive plate, a diaphragm and a negative plate which are laminated, the positive plate comprises lithium iron phosphate; the diaphragm is formed by a base film; the battery also comprises an electrolyte; the electrolyte comprises lithium bis (fluorosulfonyl) imide and lithium hexafluorophosphate; based on the total mass of the electrolyte, the mass ratio of the lithium bis (fluorosulfonyl) imide is recorded as L2, and the mass ratio of the lithium hexafluorophosphate is recorded as L1; l2 and L1 satisfy the following conditions: 0.1 < = L2 / L1 < = 4.6; the electrolyte comprises a linear organic solvent and an annular organic solvent; the linear organic solvent comprises linear carbonic ester and linear carboxylic ester, and the cyclic organic solvent comprises cyclic carbonic ester; the mass ratio of the linear organic solvent to the annular organic solvent is marked as W, and W is greater than or equal to 1; when the conditions are met, the high and low temperature performance and the safety performance of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] With the vigorous development of the global new energy industry, a green, low-carbon, circular development economic system is gradually taking shape. The start-stop power supply for automobiles mainly uses lead-acid batteries, which have low energy density, short cycle life, and high environmental pollution, which is contrary to the theme of green and low-carbon development. The 12V lithium iron phosphate battery has the characteristics of high specific energy, long cycle life, good safety performance, low cost, and environmental friendliness, which is more in line with the needs of the times for energy conservation and emission reduction. However, due to the low conductivity of the positive electrode of the 12V lithium iron phosphate battery, the internal resistance of the battery at low temperatures increases, which affects the discharge capacity and starting performance of the battery, and there is a problem of poor cold start performance at low temperatures. Summary of the invention

[0003] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium ion secondary battery. In the present invention, the diaphragm is formed by a base film, and by adjusting the porosity of the base film, the ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte, and the ratio of linear organic solvent and cyclic organic solvent in the electrolyte, the low-temperature cold start performance of the lithium iron phosphate battery can be effectively improved, the high and low temperature performance can be taken into account, and the battery safety performance can be improved.

[0004] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a separator and a negative electrode sheet arranged in a stacked manner; the positive electrode sheet comprises lithium iron phosphate;

[0005] The diaphragm is formed by a base film;

[0006] The battery further includes an electrolyte, wherein the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; based on the total mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is recorded as L2, and the mass proportion of lithium hexafluorophosphate is recorded as L1; L2 and L1 satisfy: 0.1≤L2 / L1≤4.6;

[0007] The electrolyte includes a linear organic solvent and a cyclic organic solvent; the linear organic solvent includes a linear carbonate and a linear carboxylate, and the cyclic organic solvent includes a cyclic carbonate; the mass ratio of the linear organic solvent to the cyclic organic solvent is denoted as W, W≥1.

[0008] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0009] (1) The lithium-ion secondary battery provided by the present invention can effectively improve the low-temperature cold start performance of the lithium iron phosphate battery, take into account the high and low temperature performance, and improve the battery safety performance by adopting a base film and adjusting the ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte and the ratio of linear organic solvent and cyclic organic solvent in the electrolyte.

[0010] (2) Furthermore, the lithium-ion secondary battery provided by the present invention, by adding a sulfate ester additive to the electrolyte and adjusting the mass ratio of the sulfate ester additive in the electrolyte, forms a solid electrolyte interface with better thermal stability, avoids the problem of thermal runaway of the battery caused by poor interface stability, and further improves the high-temperature safety performance of the battery; at the same time, the formed solid electrolyte interface has a lower impedance, which improves the high and low temperature performance of the battery.

[0011] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is a schematic diagram of the positive electrode structure. Figure 1 The range shown by D is the width of the ceramic coating.

[0013] Figure numerals: 1-positive electrode sheet; 2-positive electrode ear; 3-ceramic coating. DETAILED DESCRIPTION

[0014] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0015] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0016] Terminology explanation:

[0017] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0018] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a separator and a negative electrode sheet arranged in a stacked manner; the positive electrode sheet comprises lithium iron phosphate;

[0019] The diaphragm is formed by a base film;

[0020] The battery further includes an electrolyte, wherein the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; based on the total mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is recorded as L2, and the mass proportion of lithium hexafluorophosphate is recorded as L1; L2 and L1 satisfy: 0.1≤L2 / L1≤4.6;

[0021] The electrolyte includes a linear organic solvent and a cyclic organic solvent; the linear organic solvent includes a linear carbonate and a linear carboxylate, and the cyclic organic solvent includes a cyclic carbonate; the mass ratio of the linear organic solvent to the cyclic organic solvent is denoted as W, W≥1.

[0022] The lithium ion secondary battery of the present invention adopts a base film as a diaphragm, which can reduce the resistance of the diaphragm glue layer and the inorganic coating layer, and reduce the thickness of the diaphragm, and can improve the transmission efficiency of lithium ions in the battery; moreover, the present invention adds a linear organic solvent and a cyclic organic solvent to the electrolyte, and adjusts the content of the linear organic solvent to be higher than that of the cyclic organic solvent, so that the electrolyte has better dynamics and better wettability, and can fully wet the surface of the base film, so that a tight electrolyte interface is formed between the base film and the positive and negative electrodes, and the contact between the base film and the positive and negative electrodes is improved, and the resistance to lithium ion transmission is reduced, which is more conducive to improving the migration speed of lithium ions at the interface between the base film and the positive and negative electrodes; in addition, adding LiFSI lithium salt to the electrolyte can reduce and form lithium fluoride, improve the interface stability, and provide a smooth transmission channel for lithium ions, so the present invention adopts the base film as the diaphragm, and adds LiFSI and LiPF to the electrolyte at the same time. 6 , as well as linear organic solvents and cyclic organic solvents, can significantly increase the insertion and extraction speed of lithium ions at low temperatures, improve the dynamic performance of lithium iron phosphate batteries at low temperatures, reduce the migration time of lithium ions in the battery during cold start, and improve the cold start-stop effect of lithium iron phosphate batteries, effectively solving the problem of poor low-temperature cold start performance of 12V lithium iron phosphate batteries in the prior art.

[0023] In some embodiments, the base film comprises one of polyethylene, polypropylene, polyethylene and polypropylene copolymers and derivatives thereof. "Derivatives" refer to polymers obtained by introducing different functional groups into polyethylene, polypropylene, polyethylene and polypropylene copolymers or blending with other materials.

[0024] In some embodiments, the porosity of the base film is denoted as K, the mass proportion of lithium bis(fluorosulfonyl)imide (L2) and the porosity of the base film (K) satisfy: 0.02≤L2 / K≤0.7, and the value of L2 / K can be, for example, 0.02, 0.03, 0.04, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70 or any point value in the range composed of any two of the above point values, preferably 0.2≤L2 / K≤0.6. Among them, L2 preferably satisfies 1.5%≤L2≤14.5%, for example, it can be 1.5%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 14.25%, 14.5% or any point value in the range of any two of the above point values, and further preferably 2%≤L2≤12%. The heat resistance of the base film is poor. Under high temperature conditions, the base film with a higher porosity is prone to thermal shrinkage, which causes the positive and negative electrodes to contact and cause a short circuit in the battery, affecting the high temperature performance of the battery. In severe cases, it can also cause thermal runaway of the battery, leading to fire and explosion of the battery. In the present invention, when lithium bis(fluorosulfonyl)imide (LiFSI) is added to the electrolyte and the mass proportion (L2) of LiFSI and the porosity (K) of the base film are adjusted to meet the above range, LiFSI has good thermal stability and can improve the thermal stability of the electrolyte. The electrolyte with high thermal stability generates less heat at high temperature, thereby reducing the thermal stress on the diaphragm, helping to maintain the dimensional stability and mechanical strength of the base film, reducing the thermal shrinkage rate of the base film, making it less likely for the base film to shrink thermally, thereby reducing thermal runaway caused by battery short circuit and improving the high temperature safety of the battery.

[0025] In some embodiments, the porosity (K) of the base film satisfies: 20% ≤ K ≤ 60%. The porosity of the base film can be, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any point value in the range of any two of the above point values. The porosity (K) of the base film satisfies 20% ≤ K ≤ 60%, which can avoid the situation where the porosity is too high when K>60%, and the base film is more susceptible to thermal shrinkage due to temperature, resulting in a short circuit in the battery and poor safety; and avoid the situation where the porosity is too low when K<20%, resulting in deterioration of the battery dynamics.

[0026] The test methods for the porosity of the base film include true density test methods (such as dry method and volume method), which calculate the porosity of the base film by measuring the apparent density of the base film and the density of the raw materials. The raw material density refers to the true density of the material used to make the base film, such as polyethylene (PE), polypropylene (PP), etc.

[0027] The formula is: porosity = (apparent density - raw material density) / apparent density * 100%.

[0028] In some embodiments, the mass ratio of LiFSI (L2) and LiPF6 The mass proportion (L1) satisfies: 0.6≤L2 / L1≤1.7, and the value of L2 / L1 can be, for example, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or any point value in the range composed of the above two point values. Among them, L1 preferably satisfies 3%≤L1≤14%, for example, it can be 3%, 3.125%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 13.75%, 14% or any point value in the range composed of the above two point values. As the proportion of LiFSI in the electrolyte increases, the high temperature safety of the battery is further improved, but too much LiFSI will corrode the current collector and deteriorate the high temperature performance, so adjust LiFSI and LiPF 6 When the mass ratio of L2 / L1 is within the range of 0.6-1.7, it can effectively passivate the current collector and improve the high temperature performance of the battery; it can avoid excessive LiFSI and LiPF 6 Too little, the current collector cannot be LiPF 6 Effective passivation, LiFSI will react with the positive electrode current collector aluminum foil to generate Al(FSI) 3 Corrosion of the current collector results in poor contact between the positive electrode material and the current collector, thereby increasing the internal resistance of the battery and deteriorating the high-temperature performance of the battery; avoid L2 / L1<0.6, when LiFSI is too little and LiPF 6 If there is too much, the electrolyte will have poor thermal stability and cannot effectively prevent the thermal shrinkage of the base film, resulting in poor battery safety. It will also cause the electrolyte viscosity to be high and reduce the dynamics.

[0029] Exemplarily, the mass ratio (W) of the linear organic solvent to the cyclic organic solvent may be any value greater than 1, such as 1, 1.5, 2, 2.5, 3, 4, 5, etc. Cyclic carbonates have a high dielectric constant, which is conducive to the dissociation of lithium salts, but have a high viscosity and cannot meet the current high and low temperature requirements of electrolytes; linear carbonates and linear carboxylates have low dielectric constants and low viscosities. Adding linear organic solvents and adjusting the mass ratio of linear organic solvents to cyclic organic solvents can effectively solve the problem of high viscosity of the electrolyte caused by cyclic carbonates; when W<1, there are more cyclic organic solvents, the viscosity of the electrolyte increases at low temperatures, and the low temperature kinetics of the battery decreases.

[0030] In some embodiments, the mass ratio (W) of the linear organic solvent to the cyclic organic solvent satisfies: 1≤W≤19; the value of W can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or any point value in the range of any two of the above points, preferably 4≤W≤11.5. LiFSI and LiPF are added to the electrolyte. 6Although the thermal stability of the electrolyte can be improved and the battery short circuit and thermal runaway caused by thermal shrinkage of the base film can be reduced, the stability of the high-temperature interface (solid electrolyte interface) of the battery is still problematic. When the mass ratio of the linear organic solvent and the cyclic organic solvent in the electrolyte is further adjusted to meet the above range, the cyclic carbonate can form a relatively stable solid electrolyte interface on the surface of the pole piece, alleviating the problem of battery thermal runaway caused by interface instability. Furthermore, LiFSI in the electrolyte can also help to further reduce the impedance of the solid electrolyte interface formed, improve its ionic conductivity, and thus improve the kinetics; the comprehensive use of the advantages of cyclic organic solvents and linear organic solvents, combined with the use of LiFSI, can achieve the optimization of the performance of the electrolyte at high and low temperatures, so that the battery can take into account both high and low temperature performance.

[0031] In some embodiments, based on the total mass of the electrolyte, the mass proportion W1 of the linear organic solvent is 50% to 95%, and the mass proportion of the linear organic solvent can be, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or any point value in the range composed of the above two point values. The linear organic solvent includes linear carbonates and linear carboxylates, and the linear carbonates include one or more of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl propyl carbonate (MPC), preferably ethyl methyl carbonate (EMC). The linear carboxylates include one or more of propyl propionate (PP), ethyl propionate (EP), ethyl acetate (EA), methyl propionate (MP), and ethyl butyrate (EB).

[0032] In some embodiments, based on the total mass of the electrolyte, the mass proportion W2 of the cyclic organic solvent is 5% to 50%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any point value in the range of any two of the above points. The cyclic carbonate includes one or more of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), preferably ethylene carbonate (EC).

[0033] When the mass ratio of the linear organic solvent to the cyclic organic solvent and the mass proportion in the electrolyte further meet the above range, the high and low temperature performance of the battery can be further improved.

[0034] In some embodiments, the mass ratio of the linear carbonate to the linear carboxylate is 1:(0.6-1), for example, it can be 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or any point value in the range of the above two point values. The mass ratio of the linear carbonate to the linear carboxylate further meets the above range, and the combination of the two can further reduce the viscosity of the electrolyte, improve the kinetics, and greatly improve the charge and discharge efficiency of the battery at low and high temperatures, while avoiding excessive mass proportion of the linear carboxylate, which aggravates the side reaction of the pole piece and causes gas production in the battery.

[0035] In some embodiments, the thickness of the base film is recorded as dμm; the mass proportion of the linear organic solvent (W1) and the thickness of the base film (d) satisfy: 3≤W1 / d≤30, and the value of W1 / d can be, for example, 3, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30 or any point value in the range composed of the above two point values; preferably 5≤W1 / d≤20. Within this range, it can be ensured that the base surface has suitable mechanical properties and internal resistance, improve the structural stability of the battery, and maintain good dynamic performance of the battery. The present invention further satisfies the above relationship by adjusting the mass proportion of the linear organic solvent and the thickness of the base film. The larger W1 is, the viscosity of the electrolyte can be further reduced, the better the dynamics, and the problem of poor dynamics caused by the increase of d can be alleviated, the transmission rate of lithium ions can be improved, the dynamics can be improved, the cold start of the battery can be improved, and the battery short circuit and thermal runaway caused by too small thickness d can be avoided.

[0036] In some embodiments, the thickness (d) of the base film satisfies: 3≤d≤20, and the thickness of the base film can be, for example, 3μm, 6μm, 8μm, 10μm, 14μm, 16μm, 18μm, 20μm, or any point value in the range of the above two point values, preferably 5≤d≤9. The thickness of the base film further satisfies the above range, which can avoid the situation that when d>20μm, the base film is too thick, the transmission distance of lithium ions is longer, and the kinetics are worse; when d<3μm, the base film is too thin, the thermal stability is poor, and thermal shrinkage is easy to occur at high temperature, which increases the risk of short circuit and loss of control between the positive and negative electrodes.

[0037] When the content of cyclic organic solvent in the electrolyte is high, the viscosity of the electrolyte increases. The higher viscosity will reduce the diffusion rate of lithium ions, resulting in a decrease in the charge and discharge efficiency and low temperature performance of the battery. Therefore, the present invention reduces the mass proportion of cyclic organic solvent in the electrolyte, but the solid electrolyte interface formed in this way may not be uniform enough, affecting the improvement of interface stability. At the same time, LiPF in the electrolyte 6 Poor thermal stability, easily decomposed by heat to produce PF 5, which can easily destroy the solid electrolyte interface formed by the cyclic organic solvent and also affect the interface stability to a certain extent, thereby increasing the risk of thermal runaway.

[0038] To further solve the above problem, the present invention further proposes: In some embodiments, the electrolyte includes a first additive; the first additive includes a sulfate additive;

[0039] In some embodiments, the first additive includes one or more of the following compounds:

[0040]

[0041]

[0042] In some embodiments, the first additive is a sulfate additive. Based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 5%, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any point value in the range composed of any two of the above point values, preferably 0.1% to 2%.

[0043] The present invention further adds a sulfate additive to the electrolyte, and adjusts the sulfate additive to meet the above range. The sulfate additive has a strong electrochemical reduction tendency, can be reduced on the electrode surface in priority to the solvent and form protection on the electrode surface, and the formed solid electrolyte interface is more dense and smooth, has better heat resistance and structural stability, can effectively prevent the destruction of the solid electrolyte interface structure, effectively prevent the generation of electrolyte decomposition products and reduce the side reactions inside the battery, avoid the battery thermal runaway problem caused by poor interface stability, and further improve the high temperature safety performance of the battery. At the same time, the solid electrolyte interface formed by the sulfate additive has a lower impedance, so that the battery has a low irreversible capacity and good cycle performance, and can also improve the charge and discharge rate of the battery, while improving the high and low temperature performance of the battery.

[0044] In some embodiments, the electrolyte includes a second additive, and the mass percentage of the second additive is 0.1% to 5% based on the total mass of the electrolyte. The mass percentage of the second additive can be, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any point value in the range of any two of the above points, preferably 0.1% to 1%. The second additive includes one or more of thiophene, 2-fluoropyridine, tris(trimethylsilyl)phosphate (TMSP), and tris(trimethylsilyl)borate (TMSB), preferably thiophene and / or 2-fluoropyridine.

[0045] Among the second additives, TMSP and TMSB can form a stable interface film on the surface of the positive and negative electrodes, which helps to protect the electrodes, reduce the decomposition of the electrolyte, reduce the increase in the thermal shrinkage of the base film caused by the unstable interface, and improve the safety of the battery. On the other hand, TMSP and TMSB can also be used as high-voltage additives to achieve reversible lithium ion insertion / detachment at 5V in lithium-ion batteries, so that the battery has excellent high-voltage cycle stability and rate performance; thiophene can undergo electrochemical polymerization in the battery, and the polymer formed can cover the surface of the solid electrolyte interface formed by the sulfate additive to form a heat-resistant outer layer, improve the heat resistance of the interface, and prevent the interface from loosening and peeling, effectively improve the interface stability, further reduce the thermal shrinkage of the base film, and reduce the risk of battery short circuit and thermal runaway; the lone pair of electrons on the N atom in 2-fluoropyridine can coordinate with the transition metal to reduce the oxidizability of the high-valent transition metal Fe, thereby further inhibiting the oxidative decomposition of the electrolyte, reducing the corrosion of the electrolyte decomposition products on the solid electrolyte interface, and improving the high-temperature storage performance of the battery.

[0046] In some embodiments, when the second additive is thiophene and / or 2-fluoropyridine, the first additive in the electrolyte is preferably a sulfate additive shown in Formula I-3. The electrolyte contains the sulfate additive shown in Formula I-3, thiophene and / or 2-fluoropyridine at the same time, which can increase the thermal runaway temperature of the lithium-ion battery, further improve the safety of the base film, and prevent the burrs of the pole piece from piercing the diaphragm and causing a short circuit in the battery.

[0047] In some embodiments, the electrolyte includes a third additive, and the mass percentage of the third additive is 0.1% to 5% based on the total mass of the electrolyte. The mass percentage of the third additive can be, for example, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any point value in the range of any two of the above points, preferably 0.1% to 2%. The third additive includes at least one of vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), trifluoromethylethylene carbonate (TFEC), 1,2-difluoroethylene carbonate (DFEC), and bis(ethylene carbonate) (EC). Adding a third additive to the electrolyte can form a film on the negative electrode before the organic solvent, inhibit side reactions on the electrode surface, reduce the generation of side reaction products, further improve the stability of the interface film, reduce the thermal shrinkage of the base film, reduce the risk of short circuit and thermal runaway of the battery, and improve the high temperature performance of the battery.

[0048] In some embodiments, the electrolyte further includes a fourth additive, and the mass percentage of the fourth additive is 0.1% to 10% based on the total mass of the electrolyte. The mass percentage of the fourth additive can be, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range of any two of the above points, preferably 0.1% to 1%. The lithium salt additive includes lithium difluorophosphate (LiPO 2 F 2 ), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFP), lithium difluorooxalatophosphate (LiODFP), lithium tetrafluoroborate (LiBF 4 ), lithium tetrafluorooxalate phosphate (LiTFOP). Adding the fourth additive to the electrolyte can improve the ionic conductivity of the electrolyte, making the migration rate of lithium ions in the electrolyte faster, thereby further improving the high and low temperature performance of the battery.

[0049] In some embodiments, the lithium iron phosphate (LiFePO 4) The particles include primary particles and secondary particles composed of primary particles. The Dv50 of the primary particles is 0.5-1.5μm, for example, 0.5μm, 0.7μm, 0.9μm, 1.1μm, 1.3μm, 1.5μm or any point value between the ranges formed by the above two point values; the Dv50 of the secondary particles is 5-10μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm or any point value between the ranges formed by the above two point values. The particle size of lithium iron phosphate meets the above range, which can further shorten the transmission distance of lithium ions inside the positive electrode active material particles, improve the rapid transmission of lithium ions inside the particles, and thus improve the discharge performance of the battery at low temperatures.

[0050] It should be noted that the "primary particle" in the present invention refers to a single lithium iron phosphate particle; the "secondary particle" refers to a particle formed by the agglomeration of several primary particles, for example: the secondary particle is a particle formed by the agglomeration of 2 primary particles, a particle formed by the agglomeration of 5 primary particles, a particle formed by the agglomeration of 10 primary particles, a particle formed by the agglomeration of 50 primary particles, or a particle formed by the agglomeration of 100 primary particles.

[0051] Exemplarily, the Dv50 value can be measured using a laser particle size test method, for example, using a Malvern particle size tester for measurement.

[0052] In some embodiments, the positive electrode sheet includes a positive electrode collector and a positive electrode ear; at least one of the positive electrode ears is arranged on one side of the positive electrode collector along the width direction of the positive electrode sheet, and the positive electrode sheet is provided with a ceramic coating on the side in the width direction, and the ceramic coating and the positive electrode ear are located on the same side of the positive electrode sheet. The width D of the ceramic coating is 0.5mm to 10mm. The width of the ceramic coating can be, for example, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 5.5mm, 6mm, 6.5mm, 7mm, 7.5mm, 8mm, 8.5mm, 9mm, 9.5mm, 10mm or any point value in the range composed of the above two point values, preferably 1mm to 5mm. The width of the ceramic coating can be, for example, 0.5μm-10μm. When the width of the ceramic coating further meets the above range, the wider the distribution width of the ceramic coating, the lower the probability of short circuit in the battery. Since the base film has no inorganic coating, the thermal shrinkage effect is more obvious at high temperature, which can easily lead to short circuits at the edge of the pole piece. The provision of a ceramic coating can reduce the risk of short circuits, while improving the puncture performance of the edge, further improving the safety performance of the battery. In addition, it can avoid the incomplete coverage of the edge of the positive pole piece due to the small width of the ceramic coating, which can easily lead to battery short circuits. It can also avoid the ceramic coating being too wide and occupying too much pole piece position, increasing the mass of inactive substances in the pole piece, and reducing the energy density of the battery.

[0053] In some embodiments, the ceramic coating includes ceramic particles and a binder. The ceramic particles are selected from at least one of inorganic metal oxides, inorganic metal nitrides and inorganic metal salts. Exemplarily, the inorganic metal oxides include boehmite, aluminum oxide, magnesium oxide, calcium oxide, titanium dioxide, silicon dioxide and zirconium dioxide; the inorganic metal nitrides include tungsten nitride, silicon carbide, boron nitride, aluminum nitride, titanium nitride and magnesium nitride; the inorganic metal salts include barium sulfate, calcium titanate and barium titanate. The ceramic particles in the ceramic coating can form a uniform coating, making the contact between the positive electrode material particles closer and promoting the transmission of lithium ions; it can also effectively prevent the electrolyte from directly contacting the positive electrode material, reduce the corrosion of the electrolyte on the positive electrode material, thereby improving the high and low temperature performance of the battery and the battery life.

[0054] In the present invention, the binder in the ceramic coating is not specifically limited. For example, conventional binders in the art can be selected, including but not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene modified and its copolymers, polyimide, polyacrylonitrile, polymethyl methacrylate, aramid resin, polyacrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol and its copolymer-modified polyvinyl alcohol, polyvinyl acetate, polyacrylamide, phenolic resin, epoxy resin, water-based polyurethane, ethylene-vinyl acetate copolymer, polyacrylic copolymer, lithium polystyrene sulfonate, water-based silicone resin, nitrile-polyvinyl chloride blend, polyethylene oxide, styrene acrylic latex, and pure benzene latex.

[0055] In some embodiments, Figure 1 As shown, the positive electrode sheet includes a positive electrode collector (not shown in the drawings) and a positive electrode ear 2, the positive electrode ear 2 is arranged on one side of the positive electrode collector along the width direction of the positive electrode sheet, and a ceramic coating 3 is arranged on one side of the positive electrode sheet in the width direction and close to the positive electrode ear 2, and the range shown by D is the width of the ceramic coating 3.

[0056] In some embodiments, the active material of the negative electrode includes at least one of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials, and lithium-containing metal composite oxide materials.

[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0059] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0060] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0061] Example 1-1

[0062] Lithium-ion battery preparation

[0063] (1) Preparation of positive electrode sheet:

[0064] LiFePO 4), conductive carbon (Super-P) and polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone at a mass ratio of about 93.5:3:3.5, and stirred evenly to obtain a positive electrode slurry. The slurry is coated on a carbon-coated aluminum foil with a thickness of about 12 μm, dried, cold pressed, and then cut and welded to obtain a positive electrode sheet.

[0065] (2) Preparation of negative electrode sheet:

[0066] Graphite, conductive carbon (Super-P), styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC) were mixed in a solvent deionized water at a mass ratio of about 95.5:2:1.5:1, and stirred evenly to obtain a negative electrode slurry. The slurry was coated on a carbon-coated copper foil with a thickness of about 8 μm, dried, cold pressed, and then cut into pieces and welded to the tabs to obtain a negative electrode sheet.

[0067] (3) Preparation of electrolyte

[0068] In a glove box filled with argon (water <10ppm, oxygen <1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl acetate (EA) are mixed evenly, and fully dried lithium hexafluorophosphate, 10.5wt% lithium bis(fluorosulfonyl)imide, 2.5wt% vinylene carbonate, and 0.5wt% fluoroethylene carbonate are quickly added to the mixed solution based on the total mass percentage of the electrolyte, wherein the mass ratio of EC, EMC, and EA is 1:3:3, and the mass proportion of EC, EMC, and EA in the electrolyte can be obtained by calculation based on the total mass of the electrolyte. The mixed solution is stirred evenly to obtain an electrolyte.

[0069] (4) Preparation of lithium-ion batteries

[0070] The positive electrode sheet, separator (formed by base film) and negative electrode sheet prepared above are stacked by Z-type stacking machine to obtain bare battery cells without liquid injection; the bare battery cells are placed in outer packaging foil, and the prepared electrolyte is injected into the dried bare battery cells. After vacuum packaging, standing, formation, secondary sealing, sorting and other processes, the required lithium-ion battery is obtained.

[0071] (5) Battery performance test

[0072] (i) 45℃ 3C / 3C cycle test

[0073] The battery was placed in a 45°C environment for 180 minutes, and then charged at 3.0C0 constant current and constant voltage to an upper limit voltage of 3.65V, with a cut-off current of 0.05C, and then left to stand for 30 minutes; the battery was discharged at 3.0C0 constant current to 2.2V, and the initial discharge capacity C0 was recorded. When the cycle reached n times, the last discharge capacity Cn was recorded. The capacity retention rate of the nth cycle was calculated as follows: Capacity retention rate (%) = Cn / C0 × 100%

[0074] (ii) Capacity recovery test at 60℃ 100% SOC for 30 days

[0075] At 25℃, discharge at 1C0 constant current to 2.2V and set aside for 30min; charge at 1C0 constant current and constant voltage to 3.65V, cut-off current 0.05C, and set aside for 30min; discharge at 1C0 constant current to 2.2V, and get the initial capacity C1 of the battery cell; charge at 1C0 constant current and constant voltage to 3.65V, cut-off current 0.05C, and store at 60℃ for 30 days, at 25℃, discharge at 1C0 constant current to 2.2V and set aside for 30min; charge at 1C0 constant current and constant voltage to 3.65V, cut-off current 0.05C, and set aside for 30min; discharge at 1C0 constant current to 2.2V, and get the battery cell recovery capacity C30, which is calculated by the following formula: Capacity recovery rate = Cn / C30×100%.

[0076] (iii) -30℃ 50% SOC 20C 2S cold start

[0077] At 25℃, discharge the lithium-ion battery at 1C0 constant current to a cut-off voltage of 2.2V. After standing for 10min, charge at 1C0 constant current and constant voltage to 3.65V with a cut-off current of 0.05C; discharge at 1C0 constant current to a cut-off voltage of 2.2V, record the discharge capacity C0, and stand for 10min; charge at 1C0 constant current and constant voltage to 3.65V with a cut-off current of 0.05C; discharge at 1C0 constant current and constant voltage with a cut-off capacity of 50% C0; move the battery cell to a -30℃ high and low temperature box, stand for 240min, discharge at 10C constant current for 2s and record the voltage.

[0078] (iv) Thermal runaway temperature test

[0079] The battery was charged to a full charge state of 3.65V at constant current and constant voltage, and the thermal runaway temperature of the 100% SOC battery was tested using an accelerating calorimeter (ARC). The starting temperature was set to 40°C, the ending temperature to 300°C, the temperature step to 5°C, the waiting search time to 15 minutes, and the battery self-heating heating rate judgment standard to 0.02°C / min. ARC starts heating the sample from 40°C. When the temperature rises by one step, the system enters the waiting mode and tracks the exothermic reaction of the battery. After 15 minutes, the heating rate does not exceed 0.02°C / min, and the next heating step is entered until the battery self-heating heating rate exceeds 0.02°C / min. It is judged that the battery has started to self-heat. At this time, the instrument no longer heats up and monitors the battery temperature. When the battery heating rate is 1°C / min, it is judged to be the thermal runaway temperature of the battery.

[0080] (v) Acupuncture performance test

[0081] The batteries obtained in the examples and comparative examples were discharged at 25°C with a current of 0.5C to a voltage of 2.2V, then charged at a constant current of 0.5C to a voltage of 3.65V, and then charged at a constant voltage of 3.65V to a current of 0.05C. The batteries were left standing for 5 minutes. Then, a steel needle with a length of 100mm, a diameter of 5mm, and a taper of 45-60° was inserted into the middle of the battery at a speed of 25±5mm / s. After the test, the steel needle was retained in the battery for 5 minutes to observe whether the battery caught fire or smoked. If so, it was unqualified, and the pass rate of the puncture performance test was recorded.

[0082] The examples 1 to 5 and comparative examples 1 to 4 were carried out with reference to the example 1 to 1, and the main differences are shown in Table 1. Among them, the porosity of the base film was changed in the example 1. The content of LiFSI in the electrolyte was changed in the example 2. The content of LiPF in the electrolyte was changed in the example 3. 6 Example 4: Changes in LiFSI and LiPF 6 The ratio of the cyclic organic solvent to the linear organic solvent in the electrolyte was changed in Example 5. In Comparative Example 1, the porosity of the base film was too large and was not within the protection range. In Comparative Example 2, the porosity of the base film was too small and was not within the protection range. In Comparative Example 3, the LiPF 6 The proportion is small, LiFSI and LiPF 6 In Comparative Example 4, the ratio of the linear organic solvent to the cyclic organic solvent is less than 1.

[0083] Table 1

[0084]

[0085]

[0086] As can be seen from Table 1, the present invention can effectively improve the low-temperature cold start performance of the lithium iron phosphate battery, take into account the high and low temperature performance, and improve the battery safety performance by adopting a base film and adjusting the ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte and the ratio of the linear organic solvent and the cyclic organic solvent in the electrolyte.

[0087] The Example 6 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 2. Among them, the Example 6 group changed the types of linear organic solvent and cyclic organic solvent in the electrolyte.

[0088] Table 2

[0089]

[0090] It can be seen from Table 2 that the present invention uses different types of linear organic solvents and cyclic organic solvents to achieve similar effects, and can effectively improve the low-temperature cold start performance of lithium iron phosphate batteries, take into account both high and low temperature performance, and improve battery safety performance.

[0091] The Example 7 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 3. Among them, the Example 7 group changed the thickness of the base film.

[0092] Table 3

[0093]

[0094] It can be seen from Table 3 that the present invention can ensure that the base surface has suitable mechanical properties and internal resistance by adjusting the thickness of the base film, thereby improving the structural stability of the battery and maintaining good dynamic performance of the battery; by adjusting the ratio of the proportion of the linear organic solvent in the electrolyte to the thickness of the base film, the transmission rate of lithium ions can be increased, the dynamics can be improved, the cold start of the battery can be improved, and battery short circuit and thermal runaway can be avoided.

[0095] The Example 8 group was carried out in accordance with the Example 1-1, and the main differences are shown in Table 4. In the Example 8 group, the first additive was further added to the electrolyte, and the mass proportion of the first additive was changed.

[0096] Table 4

[0097] The first additive accounts for % Capacity retention rate % Capacity recovery rate % Cold start / V Thermal runaway temperature / ℃ Example 8-1 0.5% 92.76% 94.35% 2.19 182 Example 8-2 0.15% 92.45% 94.10% 2.19 182 Example 8-3 1.95% 90.22% 91.08% 2.16 182 Example 8-4 3% 88.21% 89.20% 2.09 182 Example 8-5 6% 83.65% 84.36% 2.03 182

[0098] As can be seen from Table 4, the present invention further adds a sulfate ester additive (first additive) to the electrolyte and adjusts the mass ratio of the sulfate ester additive, which can further improve the charge and discharge rate of the battery while also improving the high and low temperature performance of the battery.

[0099] Example 9 was carried out with reference to Example 8-1, and the main differences are shown in Table 5. In particular, the type of the first additive was changed in Example 8.

[0100] Table 5

[0101]

[0102] It can be seen from Table 5 that the present invention uses different types of first additives to achieve similar effects, and can effectively improve the charge and discharge rates of lithium iron phosphate batteries while also improving the high and low temperature performance of the batteries.

[0103] The Example 10 group was carried out in accordance with the Example 8-1, and the main differences are shown in Table 6. In the Example 10 group, a second additive was further added to the electrolyte, and the mass proportion of the second additive was changed.

[0104] Table 6

[0105]

[0106] It can be seen from Table 6 that the present invention further adds a second additive to the electrolyte and adjusts the mass proportion of the second additive, which can further reduce the thermal shrinkage of the base film and reduce the risk of battery short circuit and thermal runaway; reduce the corrosion of the solid electrolyte interface by the decomposition products of the electrolyte and improve the high-temperature storage performance of the battery.

[0107] Example 11 was carried out in accordance with Example 10-1, and the main differences are shown in Table 7. In particular, Example 11 changed the type of the second additive.

[0108] Table 7

[0109]

[0110] It can be seen from Table 7 that in the present invention, using different types of second additives can have a certain impact on the performance of the battery. The combination of thiophene and TMSP as the second additive can make the battery have better high-voltage cycle stability and rate performance.

[0111] Example 12 was carried out in accordance with Example 10-1, and the main differences are shown in Table 8. In Example 12, a ceramic coating was further provided in the positive electrode sheet, and the width of the ceramic coating was changed; specifically, a ceramic slurry (boehmite and PVDF, mass ratio 4:1) was coated on the current collector near the positive electrode ear side, and the width of the ceramic slurry coating was D mm.

[0112] Table 8

[0113]

[0114] It can be seen from Table 8 that the present invention can reduce the short circuit risk of the battery and improve the puncture performance of the edge by providing a ceramic coating on the positive electrode sheet and adjusting the width of the ceramic coating, thereby further improving the safety performance of the battery.

[0115] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a separator and a negative electrode sheet which are stacked; the positive electrode sheet comprises lithium iron phosphate; The diaphragm is formed by a base film; The battery further includes an electrolyte, wherein the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate; based on the total mass of the electrolyte, the mass proportion of lithium bis(fluorosulfonyl)imide is recorded as L2, and the mass proportion of lithium hexafluorophosphate is recorded as L1; L2 and L1 satisfy: 0.1≤L2 / L1≤4.6; The electrolyte includes a linear organic solvent and a cyclic organic solvent; the linear organic solvent includes a linear carbonate and a linear carboxylate, and the cyclic organic solvent includes a cyclic carbonate; the mass ratio of the linear organic solvent to the cyclic organic solvent is denoted as W, W≥1.

2. The battery according to claim 1, characterized in that The porosity of the base film is denoted as K, and K satisfies: 20%≤K≤60%; L2 and K satisfy: 0.02≤L2 / K≤0.7, preferably 0.2≤L2 / K≤0.6; Preferably, L2 satisfies: 1.5%≤L2≤14.5%.

3. The battery according to claim 2, characterized in that L2 and L1 satisfy: 0.6≤L2 / L1≤1.7; Preferably, L1 satisfies: 3%≤L1≤14%.

4. The battery according to claim 1, characterized in that W satisfies: 1≤W≤19; preferably 4≤W≤11.5; Preferably, based on the total mass of the electrolyte, the mass proportion W1 of the linear organic solvent is 50% to 95%; Preferably, based on the total mass of the electrolyte, the mass proportion W2 of the cyclic organic solvent is 5% to 50%.

5. The battery according to claim 4, characterized in that The thickness of the base film is denoted as d μm; W and d satisfy: 3≤W1 / d≤30; preferably 5≤W1 / d≤20; Preferably, d satisfies: 3≤d≤20; more preferably 5≤d≤9.

6. The battery according to any one of claims 1 to 5, characterized in that: The electrolyte includes a first additive; the first additive includes a sulfate additive; Preferably, the first additive comprises one or more of the following compounds: Preferably, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.1% to 5%.

7. The battery according to any one of claims 1 to 5, characterized in that: The electrolyte includes a second additive; the second additive includes one or more of thiophene, 2-fluoropyridine, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, more preferably thiophene and / or 2-fluoropyridine; Preferably, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.1% to 5%. 。 8. The battery according to any one of claims 1 to 5, characterized in that: The electrolyte includes a third additive, and the third additive includes at least one of vinyl ethylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, 1,2-difluoroethylene carbonate, and diethylene carbonate; Preferably, the mass percentage of the third additive is 0.1% to 5% based on the total mass of the electrolyte; And / or, the electrolyte further includes a fourth additive, the fourth additive includes a lithium salt additive; the lithium salt additive includes at least one of lithium difluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate; Preferably, based on the total mass of the electrolyte, the mass percentage of the fourth additive is 0.1% to 10%.

9. The battery according to any one of claims 1 to 5, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode ear; at least one of the positive electrode ears is arranged on one side of the positive electrode current collector along the width direction of the positive electrode sheet, and a ceramic coating is arranged on the side of the positive electrode sheet in the width direction, and the ceramic coating and the positive electrode ear are located on the same side of the positive electrode sheet; Preferably, the width D of the ceramic coating is 0.5 mm to 10 mm.

10. The battery according to any one of claims 1 to 5, characterized in that: The cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate, and butylene carbonate, preferably ethylene carbonate; And / or, the linear carbonate comprises one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, preferably ethyl methyl carbonate; And / or, the linear carboxylic acid ester includes one or more of propyl propionate, ethyl propionate, ethyl acetate, methyl propionate, and ethyl butyrate; And / or, the base film includes one of polyethylene, polypropylene, a copolymer of polyethylene and polypropylene, and derivatives thereof.

Citation Information

Patent Citations

  • Electrolyte and lithium ion battery

    CN116454396A

  • Battery with high safety performance and fast charging performance

    CN118281339A

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN118610379A

  • Lithium ion secondary battery

    CN118738569A

Cited By

  • Electrolyte, secondary battery and electronic device

    CN119742460A

  • Battery cell, battery device and electric device

    CN120565801A

  • Prismatic lithium-ion battery

    WO2026194378A1